Perceptions of Medical Students on Research Curriculum: A Cross-sectional Study - Bhadoria, Ajeet Singh; Agarwal, Shreya; Mehta, Aprajita; Sharma, Rakesh; Sinha, Smita; Bhatia, Mohit; Gupta, Bhavna; Saini, Lokesh Kumar; Goyal, Bela; Hasan, Shazia; et al. (Indian Journal of Community Health, 2024)
Introduction: Medical colleges promote research by incorporating it into the curriculum, which enables students to acknowledge it as a career prospect. The aim of the study was to assess the perceptions of medical students on research curriculum. Methods: This cross-sectional study was conducted among 544 medical students (interns and post-graduates) at AIIMS Rishikesh in 2020. Data was collected thorough online self-administered questionnaire. A comparison between groups was made using the Mann-Whitney test or chi-square test p < 0.05 was considered statistically significant. Results: Out of 544 participants, 218 (40.1%) responded with complete data. The total median score for the self-perceived ability of study participants regarding performing the research tasks differed significantly between interns and post-graduates [29.5 (24.0–34.2) vs 33 (25.2–39.7), p = 0.03]. They suggested that mandatory research projects, workshops, and training should be included in the curriculum. Conclusion: Feedback from medical students regarding the need for guided research projects, hands-on training, and inclusion of research methodology as a course in UG curriculum and provision of support in the form of incentives, academic credits, and motivation are well noted and guide the resource faculties to modify their teaching and student support programs.